Characterisation, synthesis and antimycobacterial activity of naphthoquinones isolated from Euclea natalensis - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Dissertation (MSc (Plant Physiology))--University of Pretoria, 2005.